Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Calculate the value of expresion: $$ E(x)=\frac{\sin^6 x+\cos^6 x}{\sin^4 x+\cos^4 x} $$ for $\tan(x) = 2$.

Here is the resolvation but I don't know why $\sin^6 x + \cos^6 x = ( \cos^6 x(\tan^6 x + 1) )$, see this.

Please, someone, can you explain to me why they solved it like that? :) Thanks in advance!

share|improve this question

4 Answers 4

up vote 3 down vote accepted

You can factor the term $\cos^6(x)$ from $\sin^6(x)+\cos^6(x)$ in the numerator to find: $$\cos^6(x)\left(\frac{\sin^6(x)}{\cos^6(x)}+1\right)=\cos^6(x)\left(\tan^6(x)+1\right)$$ and factor $\cos^4(x)$ from the denominator to find: $$\cos^4(x)\left(\frac{\sin^4(x)}{\cos^4(x)}+1\right)=\cos^4(x)\left(\tan^4(x)+1\right)$$ and so $$E(x)=\frac{\cos^6(x)\left(\tan^6(x)+1\right)}{\cos^4(x)\left(\tan^4(x)+1\right)}$$ So if we assume $x\neq (2k+1)\pi/2$ then we can simplify the term $\cos^4(x)$ and find: $$E(x)=\frac{\cos^2(x)\left(\tan^6(x)+1\right)}{\left(\tan^4(x)+1\right)}$$ You know that $\cos^2(x)=\frac{1}{1+\tan^2(x)}$ as an trigonometric identity. So set it in $E(x)$ and find the value.

share|improve this answer
Nice +++${}{}{}{}{}{}$ –  amWhy Feb 23 '13 at 0:04
@amWhy: It is very kind of you Amy. :-) –  Babak S. Feb 23 '13 at 3:13
It's worth the upvote :-) –  amWhy Feb 23 '13 at 3:14

Since $\frac{\sin x}{\cos x}=\tan x=2$, Simply replace $\sin x$ with $2\cos x$ and see hwo far you get. Then think about ways to express $\cos^2$ with $\tan$.

share|improve this answer

$$E(x)=\frac{\sin^6x+\cos^6x}{\sin^4x+\cos^4x}=\frac{\sin^6x+\cos^6x\over\cos^6x}{\sin^4x+\cos^4x\over\cos^6x}=\frac{\tan^6x+1}{\frac{1}{\cos^2x}(\tan^4x+1)}=$$ $$=\cos^2x\cdot\frac{2^6+1}{2^4+1}=\frac{1}{1+\tan^2x}\frac{65}{17}=\frac{1}{2^2+1}\frac{65}{17}=\frac{1}{5}\cdot\frac{5\cdot13}{17}=\frac{13}{17}$$


share|improve this answer

$$\tan x=2\implies \frac{\sin x}2=\frac{\cos x}1\implies \frac{\sin^2x}4=\frac{\cos^2x}1=\frac{\sin^2x+\cos^2x}{4+1}=\frac15$$

$$\frac{\sin^6 x+\cos^6 x}{\sin^4 x+\cos^4 x}=\frac{\left(\frac45\right)^3+\left(\frac15\right)^3}{\left(\frac45\right)^2+\left(\frac15\right)^2}=\frac{(4^3+1)5^2}{5^3(4^2+1)}=\frac{13}{17}$$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.